Hubungan Self Efficacy dan Dukungan Sosial dengan Subjective Well-Being Korban Penyalahguna Napza di Balai Rehabilitasi Sosial Napza Insyaf Medan - Berliana Silalahi; Abdul Munir; Abdul Murad (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2019)
This research aims to look at the relationship between Self Efficacy and Social Support with the Subjective Well-Being of Drug Users at the Social Rehabilitation Center for Victims of Drug Abuse "INSYAF" Medan. The research method uses quantitative research. The population of This research are 180 drug users who are undergoing rehabilitation. The sampling technique uses simple random sampling with a total sample of 80 .Data collection uses a Self Efficacy scale, a Social Support scale, a Subjective Well-Being scale. The Data analysis techniques using multiple linear regression analysis. The results showed there was a significant positive relationship between Self Efficacy and Subjective Well-Being with the correlation coefficient (R) = 0.681; sig ˂0.05. The hypothesis is accepted with an effective contribution of 46.3%. There is a positive significant relationship between Social Support and Subjective Well-Being with the correlation coefficient (R) = 0.711; Sig 0.05. The hypothesis is accepted with an effective contribution of 50.5%. There is a  positive significant relationship between Self Efficacy and Social Support with Subjective Well-Being with the correlation coefficient (R) = 0.653; sig˂0.05. The hypothesis is accepted with the effective contribution of the two independent variables to the dependent variable by 42.6%. This means that there is another factor of 57.4% of Subjective Well-Being. other factors could be income, religion, social relations, culture, self Eksteem ,etc.